Exploring mystery: can Christian meditation at school nurture students' relationships with God? - Graham, Anne (Journal of beliefs and values, 2020)
While there is growing international interest in meditation and mindfulness initiatives in schools, little research has focused on exploring the impact of such practices on students' spirituality. This paper reports data from a mixed method study involving primary school classes engaged in the regular practice of Christian meditation between Years 4 to 6 in Catholic schools in New South Wales, Australia. Student focus group data (n = 114 students) and a student survey (n = 250 students) suggest Christian meditation offers an inclusive and hospitable' space for many students, where their spiritual well-being can be nurtured, including their connection to God. However, the findings suggest that accompanying dialogue with students around the purpose and possibilities of Christian meditation may help to better situate the practice as a hospitable space' thus enabling deeper engagement with the spiritual in contemporary Catholic classrooms.